Prioritising decolonisation to encourage full-scale trade among African countries - Modiba, N. S. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
This paper explores ways and means of enhancing full-scale trade among the African countries. The paper is both conceptual and empirical in nature. Interviewing techniques and document analysis were used to collect data from three African countries regarded to be the economic superpowers of Africa, namely, Nigeria, South Africa and Algeria. Research findings revealed that firstly, the vestiges of colonialism are preventing African countries from involving themselves in full-scale trade with one another. Secondly, failure to conquer the learnt colonial thoughts and practices by the many African countries prevents full-scale trade from occurring. Thirdly, taking decisions devoid of foresight and sustainability obstruct full-scale trade among the African countries. Fourthly, ignoring the decolonisation philosophy as a 21st century gateway for African countries to free themselves from subjugation of previous years delays full-scale trade from occurring. Lastly, under-development, in the form of unavailable infrastructure, serves as a hindrance towards full-scale trade among the African countries. The researcher recommends that all African countries should regard this century as an African century where trade among them (African countries) has to soar despite the continental and global challenges they face.
Journal article published in The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Conquer; Decolonisation philosophy; Foresight; Subjugation; Vestiges; Decolonization -- Africa; Trade regulation -- Africa